Hygiene-Eliciting Brood Semiochemicals as a Tool for Assaying Honey Bee (Hymenoptera: Apidae) Colony Resistance to Varroa (Mesostigmata: Varroidae). Issue 6 (1st November 2021) - Wagoner, K; Millar, J G; Keller, J; Bello, J; Waiker, P; Schal, C; Spivak, M; Rueppell, O
Abstract: Despite numerous interventions, the ectoparasitic mite Varroa ( Varroa destructor Anderson and Trueman [Mesostigmata: Varroidae]) and the pathogens it vectors remain a primary threat to honey bee ( Apis mellifera Linnaeus [Hymenoptera: Apidae]) health. Hygienic behavior, the ability to detect, uncap, and remove unhealthy brood from the colony, has been bred for selectively for over two decades and continues to be a promising avenue for improved Varroa management. Although hygienic behavior is expressed more in Varroa- resistant colonies, hygiene does not always confer resistance to Varroa . Additionally, existing Varroa resistance selection methods trade efficacy for efficiency, because those achieving the highest levels of Varroa resistance can be time-consuming, and thus expensive and impractical for apicultural use. Here, we tested the hypothesis that hygienic response to a mixture of semiochemicals associated with Varroa -infested honey bee brood can serve as an improved tool for predicting colony-level Varroa resistance. In support of our hypothesis, we demonstrated that a mixture of the compounds ( Z )-10-tritriacontene, ( Z )-8-hentriacontene, ( Z )-8-heptadecene, and ( Z )-6-pentadecene triggers hygienic behavior in a two-hour assay, and that high-performing colonies (hygienic response to ≥60% of treated cells) have significantly lower Varroa infestations, remove significantly more introduced Varroa, and are significantly more likely to survive the winter compared to low-performing colonies (hygienic response to <60% of treated cells). We discuss the relative efficacy and efficiency of this assay for facilitating apiary management decisions and selection of Varroa -resistant honey bees, as well as the relevance of these findings to honey bee health, pollination services, and social insect communication.